2017
DOI: 10.1016/j.cct.2017.05.015
|View full text |Cite
|
Sign up to set email alerts
|

Protocol for the MATCH study (Mindfulness and Tai Chi for cancer health): A preference-based multi-site randomized comparative effectiveness trial (CET) of Mindfulness-Based Cancer Recovery (MBCR) vs. Tai Chi/Qigong (TCQ) for cancer survivors

Abstract: Purpose A growing number of cancer survivors suffer high levels of distress, depression and stress, as well as sleep disturbance, pain and fatigue. Two different mind-body interventions helpful for treating these problems are Mindfulness-Based Cancer Recovery (MBCR) and Tai Chi/Qigong (TCQ). However, while both interventions show efficacy compared to usual care, they have never been evaluated in the same study or directly compared. This study will be the first to incorporate innovative design features includin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 104 publications
1
20
0
Order By: Relevance
“…As a result, exercisers feel relaxed. Therefore, health Qigong can help exercisers calm down and relieve their anxiety (23)(24).…”
Section: Discussionmentioning
confidence: 99%
“…As a result, exercisers feel relaxed. Therefore, health Qigong can help exercisers calm down and relieve their anxiety (23)(24).…”
Section: Discussionmentioning
confidence: 99%
“…Participants were also required to collect saliva samples at home and report to a blood laboratory to provide blood samples at each assessment. A detailed description of the trial methodology has been published elsewhere [ 8 ].…”
Section: Main Textmentioning
confidence: 99%
“…Although both adherence and LTFU are grounded in participants’ intrinsic motivation to fulfil study requirements [ 6 , 7 ], it is unclear how the two are related. Given the paucity of data, the goal of the current analysis was to examine how participants’ adherence, study design elements and individual factors predicted LTFU in our ongoing trial, the MATCH study (Mindfulness and Taichi/Qigong in cancer health) (ClinicalTrials.gov: NCT02801123) [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mindful parenting has a positive influence on children’s development too. For example, high mindful parenting can positively influence the mental health of adolescents (Parent et al, 2010; Williams and Wahler, 2010; Geurtzen et al, 2015; Tak et al, 2015; Parent et al, 2016; Carlson et al, 2017). Studies have shown that parents with high levels of mindful parenting have less controlling behavior toward their children, which is known to lower self-esteem of children (Lippold et al, 2015).…”
Section: Introductionmentioning
confidence: 99%